Public Health Problems in Bangladesh: Issues and challenges (South East Asia Journal of Public Health, 2017)
In South-East Asia the main public health issues are infectious diseases and communicable diseases. Public health has improved markedly in Bangladesh over the past three decades. Nevertheless, Bangladesh faces major health challenges. A scoping study was performed according to York methodology. The study was aimed to find out the major public health issues and challenges in Bangladesh. Bangladesh has one of the worst burdens of childhood malnutrition in the world. Communicable diseases are a major cause of death and disability in Bangladesh. Unsafe food remains a major threat to public health each year, citizens suffer from the acute effects of food contaminated by microbial pathogens, chemical substances and toxins. Bangladesh still ranks among the top ten countries in the world with the highest TB burden. Pneumonia and other infections are major causes of death among young children. In Bangladesh only 1% of the population is reported to be HIV-positive, but rates are much higher among high-risk populations: injecting drug users, sex workers, and men who have sex with men. The toll of non-communicable diseases chronic diseases, cancer, diabetes, cardiovascular diseases, and chronic respiratory diseases is increasing in Bangladesh as the population becomes more urbanized. The converging pressures of global climate change and urbanization have a devastating effect on Bangladeshs most vulnerable populations. The disease burden Bangladesh is further exacerbated by unsanitary living conditions that underscore the poor economic conditions of both urban and rural home dwellers. There are still several issues that Bangladesh health care system is yet to tackle, governance, accessibility, and affordability are key issues that are preventing the implementation of solutions to the public health issues in Bangladesh.South East Asia Journal of Public Health Vol.6(2) 2016: 11-16